Pengaruh Independensi Auditor, Fee Audit dan Kompetensi Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik : Studi Empiris Pada Kantor Akuntan Publik di Bogor - Putri, Hermalia; Hardiyanto, Arief Tri; Iryani, Lia Dahlia (LP2M Politeknik Jambi, 2025)
This study is to explain the effect of auditor independence, fee audit and auditor competence on audit quality at the Public Accounting Firm (Empirical Study at the Public Accounting Firm in Bogor). This research method uses primary data with convenience sampling method.. With a population of 40 and a sample of 3 (three) KAP. The results of this study based on the test results with the t test show that auditor independence has no effect on audit quality, audit fees have no effect on audit quality and auditor competence has a significant effect on audit quality. The results of the study based on simultaneous testing with the F test show that auditor independence, audit fees and auditor competence have a joint and significant effect on audit quality.